Biomarkers of Ovarian Reserve in Women with Polycystic Ovary Syndrome - Huddleston, Heather Gibson (Seminars in Reproductive Medicine, 2013)
Recent years have seen an acceleration of research on biomarkers of ovarian reserve, with most inquiries targeted toward what these markers tell us about fertility and the reproductive lifespan. However, in the patient with polycystic ovarian syndrome (PCOS), ovarian reserve markers may provide information about the condition itself. This review will consider the use of common markers of functional ovarian reserve, including antral follicle count, ovarian volume, and anti-Müllerian hormone in the PCOS population for the purposes of diagnosing PCOS, characterizing the PCOS phenotype, and predicting response to fertility treatment.
Keywords: ovarian reserve; polycystic ovarian syndrome; anti-Müllerian hormone (AMH); antral follicle count; ovarian volume